Logistic assistance systems for collaborative supply chain planning. (18th July 2012) - Bockholt, Felix; Raabe, Wolfgang; Toth, Michael
Global market changes and new business strategies have changed logistic processes. Today, complex supply chains contain numerous manufacturing levels with long–distance transport. Effective planning and control have to follow various objectives like cost reduction, reliability and flexibility, but also ecological targets. This paper introduces Logistic Assistance Systems (LAS) for planning and decision support in supply chains. Designed as lean software systems, LAS focus on logistic planning processes and integrate selected methods for data management, information processing and supply chain planning. First achievements with LAS at Volkswagen Group are now followed by a new promising project.